Comparison of different wavelet features from EEG signals for classifying human emotions - Murugappan, Muthusamy, Dr.; Nagarajan, Ramachandran, Prof. Dr.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's hompage at http://ieeexplore.ieee.org/